Exploring nursing care needs and the role of sleep quality in women undergoing infertility treatment: implications for personalized nursing interventions - Hu, Xiaoyuan; Li, Jinxiao; Liu, Jingjing; Sun, Ningxia; Shi, Jing; Zhai, Xiaohui; Li, Lingling (Frontiers in Public Health, 2025)
ObjectiveTo investigate the status and influencing factors of nursing care needs among women undergoing infertility treatment, and to inform personalized and stage-specific nursing strategies.MethodsA cross-sectional study was conducted among 163 infertile women receiving outpatient treatment at a tertiary reproductive center in Shanghai between December 2024 and February 2025. General demographic and clinical data were collected using structured questionnaires. The Nursing Needs Assessment Scale for Infertility Patients was used to evaluate three dimensions of nursing demands. Differences in needs scores were compared across treatment stages and sleep quality levels. Pearson correlation and multiple linear regression analyses were performed to identify influencing factors.ResultsAcross all participants, the total nursing needs score averaged 37.8 ± 7.9 (range: 22–58). Mean dimension scores were 8.20 ± 2.84 for physiological and psychological needs, 15.42 ± 6.47 for information needs, and 4.37 ± 1.88 for support needs. Strong positive correlations were observed among the three dimensions (r = 0.65–0.76, all p < 0.001). Nursing needs varied significantly across treatment stages: women with ≥2 IVF cycles reported higher total needs (43.54 ± 8.75) than those in ovulation monitoring (35.29 ± 7.12) or first IVF cycle (36.42 ± 7.88; p < 0.001). Support needs differed significantly across treatment phases (p = 0.037). Sleep quality was also a key determinant: patients with very poor sleep had the highest needs (total score 48.12 ± 6.37) compared with those reporting good sleep (34.16 ± 6.89; p < 0.001). Multivariate regression confirmed that poor sleep quality predicted higher physiological and psychological needs (β = 1.087, p = 0.002), higher educational attainment was associated with stronger information needs (β = 1.669, p = 0.045), and advanced treatment stage independently predicted higher support needs (β = 0.082, p = 0.003). The adjusted R2 of the final model was 0.21.ConclusionInfertile women present with moderate to high levels of multidimensional nursing needs, which are significantly influenced by sleep quality, education level, and treatment stage. These findings highlight the importance of dynamic, individualized, and stage-specific nursing interventions to improve patient experience and treatment outcomes in assisted reproduction.